1998
DOI: 10.1074/jbc.273.32.20473
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Proline in the hsp90 Binding Region of the Glucocorticoid Receptor Is Required for hsp90 Heterocomplex Stabilization and Receptor Signaling

Abstract: Studies of hsp90 in yeast have supported the notion that this chaperone plays a critical role in signaling by steroid receptors. One limitation to these studies is that yeast expressing hsp90 mutants may also be deficient in fundamental cellular functions of the chaperone required for steroid-dependent induction of transcription. In this work, we have prepared mutants of the glucocorticoid receptor (GR) that permit analysis of hsp90 binding and transcriptional activity in cells with normal chaperone function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…One may speculate that the PPIase activity of Cpr7 may have evolved for special substrates. It is interesting to note that a conserved proline of glucocorticoid receptor is required for the stabilization of Hsp90 heterocomplexes and receptor signaling (57).…”
Section: Catalytic Activity Of the Large Immunophilins In The Accelermentioning
confidence: 99%
“…One may speculate that the PPIase activity of Cpr7 may have evolved for special substrates. It is interesting to note that a conserved proline of glucocorticoid receptor is required for the stabilization of Hsp90 heterocomplexes and receptor signaling (57).…”
Section: Catalytic Activity Of the Large Immunophilins In The Accelermentioning
confidence: 99%
“…Mutational analyses and peptide-competition studies revealed that formation of apo-GR-Hsp90 heterocomplexes that are hormone-binding competent depends on several GR subregions that cluster around the ligand-binding pocket and on three regions within the Hsp90 middle and C-terminal domain (CTD) (5,(14)(15)(16). Because these Hsp90 domains are also engaged in interactions with cochaperones, it has been uncertain whether these regions contain direct binding sites for GR.…”
mentioning
confidence: 99%
“…Despite over a decade of intense study, the basis for the recognition by Hsp90 of its diverse clients remains one of the primary mysteries in the field. Studies using site-directed and deletion mutagenesis (5)(6)(7)(8)(9)(10)(11) have identified potential sites within steroid hormone receptors and protein kinases that may be recognized by Hsp90. However, although a recent study has indicted that point mutations generated in the Cdk4 kinase (12) affect its interaction with Hsp90, no common primary, secondary, and/or tertiary structural motifs have been defined that may be responsible for Hsp90 client recognition.…”
mentioning
confidence: 99%
“…[1][2][3][4]. Current models suggest that co-chaperones may confer specificity to Hsp90 facilitated protein folding by also interacting with client targets (5,13,14). Cdc37 is one such Hsp90 co-chaperone that interacts with immature forms of Hsp90-dependent kinases (reviewed in Ref.…”
mentioning
confidence: 99%